2019
DOI: 10.1186/s12889-019-7092-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing socioeconomic disparities in sedentary behaviors in Chinese children

Abstract: Background Sedentary behaviors are prevalent in Chinese children, however, the studies on their trends and socioeconomic disparities are scarce. We examined the time trends of daily television (TV) viewing and video game playing and the associated socioeconomic factors in Chinese children in Hong Kong, the most developed and westernized city in China. Methods In a panel data study involving 538,300 primary four and 510,294 primary six students from 1999/2000 to 2008/09,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
3
14
0
1
Order By: Relevance
“…A national survey in the USA showed that on average, people spent over 80% of their time in various types of indoor spaces (Klepeis et al 2001 ). Recent surveys indicated a consistent rise of sedentary lifestyles in the general population (ACC 2019 ; Gong et al 2019 ). It is thus of particular importance to understand the dispersion, transport and deposition of respiratory droplets and associated aerosol particles in these environments for infection prevention and control.…”
Section: Transmission Of Covid-19 By Virus-laden Droplets and Indoor mentioning
confidence: 99%
“…A national survey in the USA showed that on average, people spent over 80% of their time in various types of indoor spaces (Klepeis et al 2001 ). Recent surveys indicated a consistent rise of sedentary lifestyles in the general population (ACC 2019 ; Gong et al 2019 ). It is thus of particular importance to understand the dispersion, transport and deposition of respiratory droplets and associated aerosol particles in these environments for infection prevention and control.…”
Section: Transmission Of Covid-19 By Virus-laden Droplets and Indoor mentioning
confidence: 99%
“…Conversely, in China, the most commonly used places for children's activities were public recreational facilities and business destinations outside the community (even children living in remote areas often play in these places) [37]. Recently, online and video games have become a major component of children's entertainment activities [48,49]; these have a greater impact on the scope of children's daily activities. Although Chinese online companies have developed several new technologies to strictly control children's play time and game categories; children's daily activities, especially outdoor and sports activities, are still strongly affected by video games [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An early national survey in the United States showed that in general, people spent nearly 90% of their time in various indoor environments (Klepeis et al 2001 ). The trend was reinforced in recent surveys that people increasingly adopted sedentary lifestyles by spending more time indoor (Gong et al 2019 ; Yang et al 2019 ). Since there are many common indoor sources that can emit substantial quantities of fine and ultrafine particles, which can remain suspended and accumulate in air, the wide adoption of sedentary lifestyles in the general population increases their likelihood of exposure to indoor aerosols, especially in enclosed spaces with inadequate ventilation.…”
Section: Introductionmentioning
confidence: 99%